1999
DOI: 10.1089/088922299310575
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CCR5 Is Increased in Human Monocyte-Derived Macrophages and Alveolar Macrophages in the Course of in Vivo and in Vitro Mycobacterium tuberculosis Infection

Abstract: Human immunodeficiency virus (HIV) replicates more efficiently in Mycobacterium tuberculosis (MTB)-infected macrophages than in uninfected controls. We investigated whether this may be partly explained by changes in expression of CCR5 in the course of mycobacterial infection, as this molecule has been shown to be a coreceptor for HIV entry. Since the lung is the preferential organ of HIV replication in the course of tuberculosis, we preliminarily analyzed beta-chemokine receptor expression in alveolar macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 28 publications
0
46
2
Order By: Relevance
“…For instance, morphine has been shown to modulate the expression of other cellular proteins that may induce CCR5 expression. Specifically, morphine reportedly modulates the cellular activation of NFB and TNF-␣ in macrophages (27) and interleukin-2 in lymphocytes (28); activation of NFB, TNF-␣, and interleukin-2 has been found to up-regulate CCR5 expression (10,29). Alternatively, morphine may up-regulate CCR5 by inhibiting chemokine synthesis and thus chemotaxis.…”
Section: Infection Of Cem X174 Cells With Sivmac239 or Srv-methodsmentioning
confidence: 99%
“…For instance, morphine has been shown to modulate the expression of other cellular proteins that may induce CCR5 expression. Specifically, morphine reportedly modulates the cellular activation of NFB and TNF-␣ in macrophages (27) and interleukin-2 in lymphocytes (28); activation of NFB, TNF-␣, and interleukin-2 has been found to up-regulate CCR5 expression (10,29). Alternatively, morphine may up-regulate CCR5 by inhibiting chemokine synthesis and thus chemotaxis.…”
Section: Infection Of Cem X174 Cells With Sivmac239 or Srv-methodsmentioning
confidence: 99%
“…Nonactivated AM are not equipped with effector mechanisms sufficient to clear the microbial invader. Ag-specific T cells are attracted to the site of disease by the action of locally released chemokines (12)(13)(14)(15)(16)(17)(18). Consequently, T cells secrete macrophageactivating cytokines (e.g., TNF and IFN-␥) (15) or directly lyse infected cells and contribute to the containment of mycobacterial infection (19).…”
Section: Induction Of Tnf In Human Alveolar Macrophages As a Potentiamentioning
confidence: 99%
“…10 In this context, cell activation and apoptosis can be induced by MTB infection depending upon the MOI used. 3,13,14 In fact, previously reported results showed that low levels of MTB 13 or BCG 15 prevent monocyte apoptosis whereas high amounts of the virulent strain of MTB H37Rv can induce apoptosis. 2,3 It is plausible, therefore, to hypothesize that the presence of a threshold signal, represented by the amount of mycobacteria and possibly by the amount of cell wall associated 19-kDa lipoprotein, determines whether the cell will live or die.…”
mentioning
confidence: 99%